Experiences of libraries reclassifying from the Dewey Decimal Classification to the Library of Congress Classification scheme and their implications to Silliman University Library - Yso, Lorna T.; Faderon, Rosalie B.; Sacris, Carolina N. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1984)
This study aimed to find out the experiences of nine Philippine academic libraries in reclassifying their retrospective collection from the Dewey Decimal to the Library of Congress classification scheme and their implications to Silliman University Library. Specifically, this study aimed to find out the year when these libraries started their reclassification projects, the reasons for reclassifying, the preparations that the projects entailed, the procedures adopted, the policies decided upon, the staff involved in reclassification work; the budget for the project, the problems in reclassification, and the benefits that resulted from it.
The Directory of Libraries in the Philippines was used to find out the number of libraries using LC. There are six academic, twenty-four special, and twenty-three public and government libraries using LC. The instrument used in gathering the data was the questionnaire, copies of which were personally given to the chief librarians of the eight libraries.
Some of the findings of this study showed that: 1. The earliest and latest reclassification activities in the Philippines took place in 1965 and 1981 respectively; 2. All libraries reclassified to LC because this classification scheme is found to be more fitted because it is flexible and expansive; 3. The regular cataloging staff performed both classification and reclassification processes which accounted for the slow completion of the projects. The staff of the seven libraries processed new materials over and above the reclassification of the retrospective collection; 4. There was a shortage of catalogers trained or experienced in LC. Only 55 percent had previous knowledge in using LC; 5. Funding for the reclassification projects was taken from the regular library budget; 6. Libraries were not so much concerned about reclassification costs. They proceeded with the project despite financial constraints; 7. The use of LC caused an increase in the cataloging output of six libraries. LC catalogs, like the NUC, facilitate classification or reclassification processes.
The implications of this study to Silliman University Library is that this would enable it to compare and re-assess its present condition of having different classification schemes and yet not having funds for a massive reclassification work; and to identify the alternatives in order to work out a definite course of action.
In view of the foregoing findings, it is recommended that libraries intending to reclassify should ascertain first whether there are valid and strong reasons for doing so and that reclassification should be preceded by careful planning up to the minute detail, since this is a costly and time-consuming undertaking. For those libraries which are still reclassifying , it is recommended that at least one day per week be devoted to reclassification work and that technical service operations be streamlined so that the project could be finished. For Silliman University Library, it is recommended, among other things, that total reclassification be undertaken so long as certain conditions will be met in order that its collections, which had been classified using different schemes, will be integrated.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Classification, Dewey Decimal; Classification, Library of Congress; Reclassification (Libraries).; Silliman University Library